Sexual behavior and fertility of male rats submitted to prolonged immobilization-induced stress - Almeida, S. A.; Kempinas, W. G. [UNESP]; Lamano Carvalho, T. L. (Associação Brasileira de Divulgação Científica (ABRADIC), 2000)
In order to investigate whether prolonged stress interferes with the onset of sexual behavior at puberty and with fertility at adulthood, prepubertal male Wistar rats (40 days of age) were immobilized 6 h a day for 15 days (up to early puberty) or for 60 days (until sexual maturity). Pubertal stressed rats showed a two-fold increase in the latency for the first mount (probably due to repeated aversive experience in which a change of environment was always followed by immobilization) and a 2.5-fold increase in the frequency of thrusting (indicative of enhanced sexual performance). The apparently stimulatory effect of prolonged stress on the onset of sexual behavior is discussed in terms of increased testosterone level and interference with the complex interchanges between the neurotransmitters/neuropeptides involved in the central control of male sexual activity. Adult stressed animals were mated with normal females, which became pregnant but exhibited a more than two-fold increase in both pre-implantation and post-implantation loss, probably due to a smaller rate of fertilization and/or fertilization with damaged spermatozoa.
Keywords: immobilization stress; sexual behavior; male fertility